THE INFLUENCE OF SMALL AND MEDIUM E-BUSINESS ORGANIZATION ON THE ECONOMY OF MALAYSIA - Ghazali, Abdul Jalil; Yajid, Mohd Shukri Ab; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The chief point of this examination is to explore the effect of little and medium endeavor e-business enterprise on Malaysian economy. The data had been collected from within Malaysia. A total of 200 questionnaire forms were distributed to SMEs entrepreneurs in Malaysia, where the target location was within the Klang Valley. In order to collect data in a better way, the questionnaire was sent out by mail, respondents were interviewed and a group of people identified at the specific location. All the data was processed by using SPSS and E-View. The purpose of this data analysis was to identify characteristics of the targeted 200 sample size. Moreover, it was an aim to improve the level of decision making from the data by acquired knowledge and making it comprehensible. Future studies should increase the sample size and conduct qualitative case studies, to improve the generalization of the research findings.